Manufactura y evaluación de una bomba de ariete multipulsor boxer con dos vías de carga horizontal. - Edison Fernando, Llano Toapanta (2021)
The purpose of this work was the construction of a conventional ram pump, taking as a reference the design proposed by the colleagues (Karen Tituana and Rodrigo Jiménez), and after it was built, validate the operating parameters and the performance evaluation through simulation and experimentation. Both hydraulic, volumetric and Rankine. After building this equipment, field tests were carried out to verify its functionality, verifying that the valves and springs were not operating correctly, so the valve system was modified and the springs changed. To check the modifications made to the pump, simulation software was used to validate the changes made; After this, several tests were carried out to find the operating parameters of the new pump, the most relevant information being hydraulic performance with a maximum value of 60.8% when 54 strokes per minute are reached with a flow of 32 m ^ 3 / h. This project can continue to be refined, since the systems that use ram pumps in our country are very few known, which is why this work is available to the Electro mechanics career so that its students can continue experimenting and improving the current design.